COVID-19 epidemiology and variants: new challenges and future of the pandemic - Baric, Ralph (Henry Stewart Talks, 2021)
Emergence of new variants and their new evolutionarily advantageous traits, Probability of the emergence of additional variants and a new strain of SARS-CoV-2, Potential immune escape mechanisms of a theoretical new SARS-CoV-2 strain, What can governments and individuals do to reduce the probability of emergence of additional variants, Efficacy shown to date by COVID-19 vaccines and their projected impact in controlling the pandemic, Update on current COVID-19 treatments (including convalescent antibody therapy, Remdisivir and dexamethasone) and the importance of the time window for their administration